Dermoscopy in differential diagnosis of inflammatory dermatoses and mycosis fungoides - Bilgic, Sultan A.; Cicek, Demet; Demir, Betul (Wiley, 2020)
Background The use of dermoscopy for the evaluation of various inflammatory dermatoses has witnessed a gradual increase in recent years. The present study describes and highlights the importance of dermoscopic findings in the differential diagnosis of plaque psoriasis (PP), lichen planus (LP), mycosis fungoides (MF), pityriasis rosea (PR), and nummular dermatitis (ND) that mostly involve the trunk. Methods The study included 150 cases (PP:50, LP:30, MF:20, PR:30, ND:20). The lesions were inspected using a polarized dermoscope. The dermoscopic findings of each lesion were evaluated for background color, type, and distribution of vessels, color and distribution of scales, and other additional findings. Results When the patient groups were evaluated for background color, yellow color was prominent in PR, and light and dull red color was prominent in other groups. Dotted vessels were prominent in PP, PR, and ND, and dotted + linear vessels were significantly more prominent in MF and LP. In the evaluation of the distribution pattern of vessels, PP showed regular, LP showed peripheral, and PR, MF, and ND showed patchy distribution patterns. White scales were prominent in PP, PR, and MF, and yellow-white scales were prominent in LP and ND. Only PR had a predominant peripheral distribution of scales, while other groups had a patchy distribution. Conclusions In conclusion, it was observed that PP, LP, MF, PR, and ND exhibited specific dermoscopic patterns that might be useful in clinical diagnosis.
Keywords: Lichen-Planus; Psoriasis; Features